Variation in carbon cycling among four tree species in a tropical rain forest - Asao, Shinichi, author; Parton, William J., advisor; Ryan, Michael G., advisor; Bauerle, William L., committee member; Knapp, Alan K., committee member (Colorado State University. Libraries, 2014)
To view the abstract, please see the full text of the document.
Keywords: allocation; ecophysiology; ecosystem; photosynthesis; production; respiration